PERAN ORGANISASI PROFESI DALAM PENYELESAIAN SENGKETA ETIKA: STUDI LITERATUR TENTANG FUNGSI MAJELIS KEHORMATAN DAN JALUR ETIKA PROFESI - Hotmaria Hertawaty Sijabat (Jurnal Salome : Multidisipliner Keilmuan, 2025)
The role of professional organisations in resolving ethical disputes is crucial to maintaining the integrity and professionalism of their members. This literature review examines the function of the Ethics Council and professional ethics channels as mechanisms for resolving ethical disputes. The Ethics Council acts as an independent body that handles investigations, mediation, and enforcement of the code of ethics in a fair and transparent manner, while also protecting the reputation of the profession. Meanwhile, the professional ethics channel provides efficient and educational formal procedures for members to resolve disputes internally, prioritising mediation and formal investigations without having to involve external legal processes. These two mechanisms form a comprehensive ethical dispute resolution system, maintaining organisational harmony and increasing public trust in the profession.